Limited effect of adaptive immune response to control encephalitozoonosis - Sak, B; Kotková, M; Hlásková, L; Kváč, M (Parasite immunology, 2017)
This study revises our understanding of the effectiveness of cell-mediated adaptive immunity and treatment against microsporidia using molecular detection and quantification of microsporidia in immunocompetent C57Bl/6 and immunodeficient CD4-/-and CD8-/-mice for the first time. We demonstrate an intense dissemination of microsporidia into most organs within the first weeks post-infection in all strains of mice, followed by a chronic infection characterized by microsporidia persistence in CD4-/-and C57Bl/6 mice and a lethal outcome for CD8-/-mice. Albendazole application reduces microsporidia burden in C57Bl/6 and CD4-/-mice, whereas CD8-/-mice experience only a temporary effect of the treatment. Surprisingly, treated CD8-/-mice survived the entire experimental duration despite enormous microsporidia burden. On the basis of our results, we conclude that microsporidia survive despite the presence of immune mechanisms and treatments that are currently considered to be effective and therefore that CD8 T lymphocytes represent a major, but not sole effector mechanism controlling microsporidiosis. Furthermore, the survival of mice does not correspond to spore burden, which provides new insight into latent microsporidiosis from an epidemiological point of view.
Keywords: Animals; adaptivní imunita; Anthelmintics; Encephalitozoonosis; Mice, Knockout; myši knockoutované; Adaptive Immunity; Mice; buněčná imunita; CD8-Positive T-Lymphocytes; lymfopenie; Albendazole; myši; Encephalitozoon cuniculi; Lymphopenia; CD8-pozitivní T-lymfocyty; anthelmintika; Immunity, Cellular; CD4-Positive T-Lymphocytes; zvířata; encephalitozoonóza; Mice, Inbred C57BL; albendazol; myši inbrední C57BL; CD4-pozitivní T-lymfocyty